2009
DOI: 10.1093/jac/dkp381
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing antibiotic activity: a strategy to control Acinetobacter infections

Abstract: Susceptibility of MDR A. baumannii to a variety of antibiotics was enhanced in the presence of ellagic and tannic acids. The use of such plant compounds might provide effective treatments for resistant Gram-negative bacterial infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 43 publications
0
60
1
1
Order By: Relevance
“…Geraniol significantly increases the efficacy of beta-lactams, quinolones, and chloramphenicol [63]. It is observed that at 40 mM, ellagic and tannic acids enhanced the activity of novobiocin, coumermycin, clorobiocin, rifampicin and fusidic acid against A. baumannii [73].…”
Section: Interaction Between Herbal Drugs and Antibioticsmentioning
confidence: 99%
“…Geraniol significantly increases the efficacy of beta-lactams, quinolones, and chloramphenicol [63]. It is observed that at 40 mM, ellagic and tannic acids enhanced the activity of novobiocin, coumermycin, clorobiocin, rifampicin and fusidic acid against A. baumannii [73].…”
Section: Interaction Between Herbal Drugs and Antibioticsmentioning
confidence: 99%
“…Addressing the long-term challenge posed by antibiotic resistant pathogens will require therapeutic strategies 10 and compound development 46,47 that considers ways to manipulate and slow the evolution of resistance.…”
Section: Towards Therapies Informed By Evolutionmentioning
confidence: 99%
“…The medical literature reported that many phenolic compounds of plant extracts enhance the potential of synthetic antibiotics against A. baumannii in vitro (Miyasaki et al, 2013). For instance, activity of rifampicin, coumermycin, fusidic acid, novobiocin, and chlorobiocin was enhanced by tannic acid and ellagic acid against A. baumannii in vitro (Chusri et al, 2009). Even synergy was observed between topical mafenide and green tea polyphenol against multi-drug resistance Acinetobacter baumannii in-vitro (Osterburg et al, 2009), while no effect of synergy was noted between any antibiotics for Gram-negative bacteria and norwogonin.…”
Section: Plant Active Compounds Against Acinetobacter Baumanniimentioning
confidence: 99%